Respuestas

2012-07-13T16:14:19+02:00

((3X-20)/10) - ((X-8)/2) = ((20-3X)/5) - 11 => ((3X-20-5X+40)/10) = ((20-3X+55)/5) =>

 

((-2X + 20)/10) = (75 - 3X)/5 => (-2X + 20) = 10x((75-3X)/5) => -2X - 20 = 2x(75-3X) => -2X+20 = 150 - 6X => -2X + 6X = 150 - 20 => 4X = 130 => X = 130 / 4 => X = 65 / 2

2012-07-13T19:16:01+02:00

\frac{3x -20}{10} -\frac{x-8}{2} =\frac{20-3x}{5} +11

 

\frac{3x -20 -5(x-8)}{10} =\frac{20-3x + 55}{5}

 

\frac{3x -20 -5x+40}{10} =\frac{75-3x}{5}

 

\frac{-2x +20}{10} =\frac{75-3x}{5}

 

5(-2x +20) = 10 (75 -3x)

 

-10x +100 = 750- 30x

 

-10x +30x = 750 -100

 

20x = 650 

 

x = 32.5